Reducción de defectos de calidad en el proceso de fabricación de envases de licores en la empresa Owens Illinois Perú S.A. - Mendoza Mendoza, Aldo Cesar (2021)
In recent decades, the company Owens Illinois Peru S.A., has been almost the only manufacturer of glass containers in the country, encouraging sustained growth of its customers, offering flexibility, develop designs and quality; this in a global context, where at the same time, O-I is a world leader in the manufacture of glass containers, where of the important characteristics is: the wealth of information on processes and technology across various countries and plants throughout the world. At present, the company Owens Illinois Perú S.A., in the process of manufacturing glass containers, it has opportunities for improvement with respect to an important sector that has been growing steadily and is threatened by new competitors from other countries or to protect national customers from global brands positioned in the world of liquors, which enter the national market. This project, studies the improvements around the packaging manufacturing process with a focus on the liquor sector and the opportunities that exist to reduce the costs of poor quality, the costs associated with claims, observations that may exist in customers, affecting the productivity and especially blocking important inventories that put in danger the continuity of the business; all this to ensure the sustainability and growth of both parties.